The indicator side of tree microhabitats: A multi‐taxon approach based on bats, birds and saproxylic beetles. Issue 5 (6th June 2018) - Paillet, Yoan; Archaux, Frédéric; du Puy, Solène; Bouget, Christophe; Boulanger, Vincent; Debaive, Nicolas; Gilg, Olivier; Gosselin, Frédéric; Guilbert, Eric
Abstract: National and international forest biodiversity assessments largely rely on indirect indicators, based on elements of forest structure that are used as surrogates for species diversity. These proxies are reputedly easier and cheaper to assess than biodiversity. Tree microhabitats—tree‐borne singularities such as cavities, conks of fungi or bark characteristics—have gained attention as potential forest biodiversity indicators. However, as with most biodiversity indicators, there is a lack of scientific evidence documenting their quantitative link with the biodiversity they are supposed to assess. We explored the link between microhabitat indices and the richness and abundance of three taxonomic groups: bats, birds and saproxylic beetles. Using a nation‐wide multi‐taxon sampling design in France, we compared 213 plots located inside and outside strict forest reserves. We hypothesized that the positive effect setting aside forest reserves has on biodiversity conservation is indirectly due to an increase in the proportion of large structural elements (e.g., living trees, standing and lying deadwood). These, in turn, are likely to favour the quantity and diversity of microhabitats. We analysed the relationship between the abundance and species richness of different groups and guilds (e.g., red‐listed species, forest specialists, cavity dwellers) and microhabitat density and diversity. We then used confirmatory structural equation models to assess the direct and indirect effects of management abandonment, large structural elements and microhabitats on the biodiversity of the target species. For several groups of birds and bats, the indirect effect of management abandonment and large structural elements on biodiversity was mediated by microhabitats. However, the magnitude of the link between microhabitat indices and biodiversity was moderate. In particular, saproxylic beetles' biodiversity was poorly explained by microhabitats, large structural elements or management abandonment. Synthesis and applications . Tree microhabitats may serve as indicators for bats and birds, but they are not a universal biodiversity indicator. Rather, compared to large structural elements, they most likely have a complementary role to biodiversity. In terms of forest management and conservation, preserving diversity of microhabitats at the local scale benefits several groups of both bats and birds. Abstract : Tree microhabitats may serve as indicators for bats and birds, but they are not a universal biodiversity indicator. Rather, compared to large structural elements, they most likely have a complementary role to biodiversity. In terms of forest management and conservation, preserving diversity of microhabitats at the local scale benefits several groups of both bats and birds.